1999
DOI: 10.1093/ajcn/70.5.811
|View full text |Cite
|
Sign up to set email alerts
|

Obesity at the age of 50 y in men and women exposed to famine prenatally

Abstract: Maternal malnutrition during early gestation was associated with higher BMI and waist circumference in 50-y-old women but not in men. These findings suggest that pertubations of central endocrine regulatory systems established in early gestation may contribute to the development of abdominal obesity in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
636
8
20

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,019 publications
(705 citation statements)
references
References 20 publications
41
636
8
20
Order By: Relevance
“…However, similar findings among humans are limited. Some studies of the Dutch Famine suggest that early-gestation exposure was associated with obesity among women (32) and with an atherogenic lipid profile (33) independent of effects on size at birth. Similarly, maternal bereavement before or during pregnancy increases risk of offspring overweight independent of birth weight (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, similar findings among humans are limited. Some studies of the Dutch Famine suggest that early-gestation exposure was associated with obesity among women (32) and with an atherogenic lipid profile (33) independent of effects on size at birth. Similarly, maternal bereavement before or during pregnancy increases risk of offspring overweight independent of birth weight (21).…”
Section: Discussionmentioning
confidence: 99%
“…11 Our findings are in line with previous studies showing associations of both low and high birth weight with an increased risk of developing overweight. [49][50][51] Recent studies have reported that this might be dependent on programming of lean body mass as well as programming of fat mass. The ALSPAC study found a positive association of birth weight with both lean body mass and total body fat.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of young adult men and middle-aged women exposed to intrauterine famine during the Dutch Hunger Winter of 1944 indicate that obesity may be in part determined through nutritional programming in early to mid-gestation. 31,32 Law et al 33 noted that waist-hip ratio, an indicator of how body fat is distributed, was negatively related to weight at birth suggesting that abdominal fatness is programmed before birth. The Nurses Health Study indicated a U-shaped relationship between birth weight and later body weight, with higher body mass index observed in women in the lowest and highest birth weight groupings.…”
Section: Discussionmentioning
confidence: 99%